Valuasi PT. Saliman Riyanto Group Menggunakan Metode Discounted Cash Flow Dan Strategi Penetapan Harga Saham Perdana (Initial Public Offering) - Ahmad Junaedi; Mohammad. Bukhori; Tin Agustina Karnawati (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
This study aims to determine the valuation of PT. Saliman Riyanto Group and determine the indication of the fair value of the share price to be released if the company makes an offer to potential investors either through an initial public offering (IPO) or closed offering using fundamental analysis, called the Discounted Cash Flow (DCF) method. As a private company, it is a difficulty for investors to know the value or valuation of PT. Saliman Riyanto Group and what is a reasonable price per share. This is a descriptive research with a quantitative approach. This study used techniques of data analysis, called the calculation of financial ratios, using the DCF formula. The results of research used the DCF method show the value (valuation) of PT. Saliman Riyanto Group is Rp. 494,257,978,926.22, - and the fair share price to be released in the IPO is Rp. 7,776,365.94